The pursuit of happyness - Gardner, Chris (Chris P.); Troupe, Quincy; Rivas, Mim Eichler (New York : Amistad, 2006)
At the age of twenty, African American Gardner arrived in San Francisco to pursue a promising career in medicine. However, he surprised everyone and himself by setting his sights on the competitive world of high finance. Yet no sooner had he landed an entry level position at a prestigious firm, Gardner found himself caught in a web of challenging circumstances that left him part of the city's working homeless with his toddler son. Motivated by the promise he made to himself as a fatherless child to never abandon his own children, the two spent almost a year in shelters, "HO-tels", and soup-lines. Never giving in to despair, Gardner went from being part of the city's invisible to being a powerful player in its financial district.
Keywords: Gardner, Chris; Gardner Rich & Co; Stockbrokers -- United States -- Biography